Enzymatic hydrolysis of delignified bagasse polysaccharides - Adsul, Mukund G.; Ghule, J. E.; Shaikh, H.; Singh, R.; Bastawade, Kulbhushan B.; Gokhale, D. V.; Varma, Anjanikumar (Carbohydrate Polymers, 2005)
Sugarcane bagasse, consisting of cellulose, xylan, and lignin, was chemically treated to generate bagasse samples with continuously decreasing content of lignin. These bagasse samples were hydrolyzed by cellulase and xylanase enzymes, produced earlier by Penicillium janthinellum NCIM 1171 in the same bagasse polysaccharides production medium. The hydrolysis was carried out by using different concentrations of the enzymes at two different temperatures, 30 and 50 degrees C, taking hydrolysis of Avicel as control. It was found that while the maximum hydrolysis for Avicel was 70% that of some of the bagasse polysaccharides was as high as 95%. The products of hydrolysis were glucose, xylose, and arabinose, as confirmed by high pressure ion chromatography (HPIC). It is interesting to note that arabinose, which constitutes about 10% of the weight of bagasse xylan, could also be released easily by the enzymes. Also, the initial rates of hydrolysis was found to be much higher for the bagasse polysaccharides, and in some cases about 90% of the hydrolysis occurred within 20 h. Amongst all bagasse samples, the sample with (Kappa no. 1.2, lignin content 0.18%) gave the highest degree of hydrolysis at 50 degrees C. Even the bagasse polysaccharide with Kappa no. 16.8 (lignin content 2.5%) underwent greater extent of hydrolysis than Avicel. Apparently, the delignified bagasse medium appears to be a facile medium for the combined hydrolytic action of the cellulase and xylanase enzymes. Considering that sugarcane bagasse is a waste biomass material available in abundance annually, this methodology can be used to value-add to this biomass to produce sugars, which can be fermented to produce biofuels like ethanol. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: bagasse polysaccharides; Cellulase; chemical treatment; Enzymatic hydrolysis; Penicillium janthinellum; Sugarcane bagasse; Xylanase

Environment friendly crosslinked chitosan as a matrix for selective adsorption and purification of lipase of aspergillus niger - Trimukhe, K. D.; Mahadik, N. D.; Gokhale, D. V.; Varma, Anjanikumar (International Journal of Biological Macromolecules, 2008)
Chitosan and its derivatives have been used as affinity matrices for purification of lipase from Aspergillus niger NCIM 1207. Trimellitic anhydride (TMA)-crosslinked deacetylated chitin adsorbed lipase selectively, yielding approximately 5-fold purification of the crude lipase with 70% yield. Further 9-fold purification occurred on eluting through Sephacryl-100. These results suggest that chitosan derivatives can be used as inexpensive biopolymer matrices for the purification of lipases for industrial applications. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Chitosan; Lipase; Matrix; Purification

Enhanced enzymatic hydrolysis of cellulose by partial modification of its chemical structure - Shaikh, H. M.; Adsul, Mukund G.; Gokhale, D. V.; Varma, Anjanikumar (Carbohydrate Polymers, 2011)
A series of 2,3-dialdehyde celluloses with different degrees of oxidation were used for deriving corresponding dicarboxylate, dicarboxy, and Schiff's base cellulose derivatives. The dialdehyde cellulose was hydrolyzed by cellulase to a lower extent than the starting cellulose, except at high levels of aldehyde content (above 50%). For dicarboxylate and dicarboxy celluloses, the highest level of oxidized NaDCC and DCC hydrolysed up to 70 and 60% respectively which was 3-4 times more than cellulose. The 2,3-dioxime cellulose derivative hydrolyzes only up to 16.3% for the highest level of oxidized dioxime. In the case of 2,3-diethylimine cellulose, all derivatives hydrolyse faster than the native cellulose. Up to 75% hydrolysis was observed for 2,3-diethyimine cellulose-50, 2,3-dipropylimine and 2,3-dibutylimine cellulose. The 2,3-dibenzylimine cellulose hydrolyses a little slower than the alkylimine derivatives. The 2,3-dihydrazone cellulose derivatives with all level of oxidation showed resistance towards enzymatic hydrolysis. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: 2; 3-Dialdehyde celluloses; 3-Dibenzylimine cellulose; 3-Dibutylimine cellulose; 3-Dicarboxy celluloses; 3-Diethyimine cellulose; 3-Dihydrazone cellulose; 3-Dipropylimine cellulose; Cellulase; Enzymatic hydrolysis